Q-FACTOR OF A RECTANGULAR RESONATOR WITH A VARIABLE NUMBER OF DIELECTRIC INHOMOGENEITIES - Samoylik, S. S.; Bondarev, V. P. (Radio Electronics, Computer Science, Control, 2024)
The calculation of a rectangular resonator with а complex dielectric loading is solved by the method of integral equations of microscopic electrodynamics. The carried out numerical analysis enabled to calculate Q-qualities of the rectangular resonator, for various Нm0n types of fluctuations depending on parameters of complex dielectric filling.